20% Hike in Panorama $$ - Smith, Keith (Daily Express)
Pan Trinbago has "reluctantly" accepted a 20 per cent increase in Panorama prize money from government. Pan Trinbago's President Arnim Smith stated that the reason for its dissatisfaction with the arbitrary manner in which government arrived at its 20 per cent offer. The prizes for the National Panorama Championship and Pan-Round-Neck are listed.
Keywords: Steel bands (Music) -- Competitions -- Trinidad and Tobago; Panorama (Musical festival); Pan Trinbago (Organization); Steel bands (Music) -- Trinidad and Tobago -- Finance